Possibilities of energy-saving in processes of evaporation of aqueous solutions - A. V. Koval; M. K. Zakharov; G. A. Nosov (Тонкие химические технологии)
An improved scheme of multiple-effect evaporator is suggested. Method of calculation of units' dimensions is given. Variants of optimal energy exploitation of these evaportators were found